Occurrence of extreme temperature events – A Probable risk on natural rubber cultivation - Jayasooryan, K.K.; Satheesh, P.R.; Krishnakumar, R.; Jacob, James (Journal of Plantation Crops, 2015)
<span style="line-height: 107%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-bidi-language: HI; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US;" lang="EN-GB">Climate change and occurrence of extreme temperature events were studied in Kottayam, a major rubber growing district in Kerala. Occurrence of extreme temperature events can affect the livelihood of rubber growers apart from the ecological impact. The present study was conducted by analysing the occurrence of extreme temperature events in the past 40 years (1970-2010) using the RClimDex package developed by the Expert Team on Climate Change Detection Monitoring and Indices (ETCCDMI), Canada. Temporal variations in trends of occurrence of extreme temperature events were tested with Mann-Kendall trend analysis. The 5-year diurnal temperature range (DTR, difference between monthly mean maximum and minimum temperatures) increased from 7.8 (during 1970-1974) to 9.2 0C (during 2006-2010). The monthly mean maximum temperature increased by 0.035 0C per year. Frequency of occurrence of hot days increased at a rate of 0.56 per cent per year and the highest temperature recorded in a month showed an increase of 0.038 0C per year. As observed, the increasing trends in the occurrence of extreme temperature events may eventually lead to the warming up of the region in future. The study indicates that the projected warming tendency in the traditional rubber growing regions of India may affect the rubber cultivation adversely.